2 Non-uniformity in pre-insertional achilles tendon is not influenced by changing knee angle during isometric contractions. (April 2019) - Bogaerts, Stijn; De Brito Carvalho, Catarina; De Groef, An; Peers, Koen
Abstract : Introduction: Mechanical loading in Achilles tendinopathy, e.g. eccentric exercise, is commonly performed in both extended and flexed knee positions. The goal of this study was to evaluate the impact of this changing knee angle on the non-uniform behaviour in the Achilles tendon, i.e. superficial-to-deep variation in displacement with highest displacement in the deep layer. It was hypothesized that a flexed knee position would lead to a more non-uniform behaviour, due to greater differential loading of soleus versus gastrocnemius in this position. Materials and methods: Nineteen healthy subjects participated in this study. A high-spatial and high-temporal resolution US system was used to acquire 2D+time ultrasound images during an isometric contraction at 25%, 50% and 75% MVC in the extended and flexed knee position. Local tendon tissue displacement of the different tendon layers and normalized displacement ratio, a measure for non-uniformity, were calculated. Results: Contrary to the hypothesis, it was found that the non-uniform deformation, with highest displacement in the deep tendon layer, is consistently present and not influenced by a change in knee angle. Conclusion: From clinical perspective, this might indicate the absence of a mechanical rationale for a change in knee angle during loading exercises. Additionally, it was found that despite reaching high levels of force, the contribution of the AT to this deformation is sometimes unexpectedly smaller, potentially due to compensatory actions. This is relevant for AT rehabilitation as the goal there is to reach specific local tendon loading.